Performance and NOx emissions of a diesel engine with water injection - Aziz, Amir; Mamat, Rizalman; Abdullah, Abdul Adam; Hagos, Ftwi Yohaness; Ali, Obed Majeed (2017)
The emission like nitrogen oxide is an unwanted pollutant from diesel engines. One out of many methods to decrease the nitrogen oxides is the water injection. One measure to inject water into the engine is the injection into the intake manifold. The injection of the water is possible at three different locations at the investigated engine. One injection is with the airflow, the other is against the airflow and the third is towards the airflow. Water storage and the pressure supply for the injector are developed to support the injector with water under pressure. The amount of injected water is being varied from 0 to 100% water/fuel ratio in steps of 20%. Parallel to this work a simulation model of the engine is created to simulate the behaviour of the water injection. The simulation results show a decrease of the nitrogen oxide, carbon monoxide and carbon dioxide emissions as well as an increase of the performance and a decrease of the fuel consumption. These results are compared with the measurement results from the engine on the test bed. The results of the test runs show the same tendency as the simulation. The values of the simulated and measured parameters differ slightly due to estimation in the simulation model and tolerances of the measurement equipment and test bed. The temperature and the nitrogen oxide emission decrease drastically. This benefit has the drawback of an increase of the particle matter emission. The combustion process is slightly affected by the water injection. The performance parameters are very slightly affected with a little decrease of the efficiency and torque. The fuel consumption is constant with the water injection.